The Epistemological Reading of Religious Knowledge in the Thought of ʻAbd Al-Karīm Soroush - Mokhtari, Omar (Al-Jami'ah: Journal of Islamic Studies, 2024)
This study explores the epistemological dimensions of religious reform advanced by ʻAbd al-Karīm Soroush within the framework of ʻilm al-kalām al-jadīd (modern Islamic theology). It examines how Soroush conceptualizes the relationship between religion (al-dīn) and religious knowledge (al-maʻrifah al-dīniyyah), positing that the latter is inherently dynamic, historically situated, and epistemologically contingent. At the heart of his framework lies the assertion that religious knowledge is not fixed but evolves in tandem with developments in human understanding, cultural contexts, and scientific progress. Employing both epistemological and hermeneutical methodologies, this study analyzes Soroush’s engagement with contemporary philosophy, science, the human sciences, and Islamic mysticism (ṣūfism). It argues that Soroush advocates a clear distinction between the divine essence of religion and the human endeavor to understand it—an approach that challenges absolutist readings of scripture and affirms the relative, interpretive nature of religious knowledge. Furthermore, the study highlights Soroush’s acknowledgment of the interdependence between religious and non-religious forms of knowledge, emphasizing their mutual borrowing and discursive entanglement. His intellectual orientation reveals a deliberate engagement with the foundational critiques of Western modernity, particularly those articulated by reformist Christian theologians and philosophers. This is most evident in his seminal works al-Qabd wa al-Basṭ fī al-Syarīʻah (The Expansion and Contraction of Religious Knowledge) and al-Ṣirāṭ al-Mustaqīm (The Straight Paths), which articulate a sophisticated vision of reform grounded in both tradition and critical modern thought.[Tulisan ini mengkaji hakikat pembaharuan dalam warisan keagamaan yang diserukan oleh ʻAbd al-Karīm Soroush dalam lingkup ilmu kalam kontemporer. Fokus utamanya adalah menyingkap berbagai bentuk pendekatan terhadap agama dan pengetahuannya, serta bagaimana pemikir ini mengkaji pengetahuan keagamaan dengan perangkat epistemologis dan hermeneutik untuk membaca, membedah, dan menganalisis pengetahuan manusia, dalam rangka menangkap dimensi yang tetap dan yang berubah dalam agama. Penelitian ini juga menekankan prinsip dasar bahwa pengetahuan keagamaan bersifat dinamis dan senantiasa mengalami transformasi. Dengan pembacaan kritis terhadap konsep dīn (agama) dan al- maʻrifah al-dīniyyah (pengetahuan keagamaan), penelitian ini memanfaatkan pendekatan epistemologis dan hermeneutik, serta temuan ilmu pengetahuan dan filsafat kontemporer, ilmu-ilmu sosial dan kemanusiaan, serta tasawuf Islam. Penelitian ini menyimpulkan bahwa ʻAbd al-Karīm Soroush menekankan pentingnya pemisahan antara agama dan pengetahuan yang lahir darinya. Pengetahuan keagamaan hanyalah salah satu bentuk dari pengetahuan manusia yang bersifat relatif dan --oleh karena itu-- senantiasa dapat berubah dan berkembang, karena merupakan hasil pemahaman manusia terhadap agama yang bersifat historis. Soroush juga menegaskan adanya keterkaitan erat antara pengetahuan keagamaan dan pengetahuan non-keagamaan, yang saling memberi dan menerima. Dengan demikian, proses memahami agama dan membaca teks-teks sucinya merupakan proyek yang bersifat relatif dan tidak mungkin mencapai kesempurnaan atau kebenaran absolut. Soroush berupaya mendekati agama dan pengetahuan keagamaan dengan menggunakan pendekatan-pendekatan dari modernitas Barat, sebagaimana yang telah diterapkan dalam teologi Kristen oleh para filsuf dan reformis sebelumnya, sebagaimana dijelaskan dalam karyanya al-Qabḍ wa al-Basṭ fī al-Syarīʻah dan al-Ṣirāṭ al-Mustaqīm.